SOX9 duplication linked to intersex in deer. - Regina Kropatsch (Public Library of Science (PLoS), 2013)
A complex network of genes determines sex in mammals. Here, we studied a European roe deer with an intersex phenotype that was consistent with a XY genotype with incomplete male-determination. Whole genome sequencing and quantitative real-time PCR analyses revealed a triple dose of the SOX9 gene, allowing insights into a new genetic defect in a wild animal.